Modern database management : VI Edition. Jeffrey A. Hoffer, Mary B. Prescott, Fred R. McFadden Prentice Hall, Upper Saddle River, NJ, 2002 - Bertone, Rodolfo Alfredo (2003)
This book provides an excellent foundation for the principles of database and data management. It explains some of the more difficult concepts fairly well. The book is meant for an introductory course in database management which is usually required as part of a computer science departments.